Understanding written message framing, motivation, and performance in competitive cyclists - Fasczewski, K. S.; Bramblett, P. N.; Bobo, L. K.; Peterman, J.; Shanely, R. A. (The Sport Journal, 2023)
Purpose An athlete`s motivation and sport performance is impacted by their environment, including the interpersonal relationship between athlete and coach. What messages the coach conveys, and how those messages are received, can impact performance. Conveying messages via controlling message framing (dictating goals and outcomes) or informational/supportive message framing (providing information and recognizing effort) may impact the athlete`s perceptions of the environment and alter motivation, thus impacting performance. Endurance sports, such as cycling, require high amounts of self-determined motivation due to the duration and solo nature of training. Often the primary interaction with the coach is through online written communication. As such, the goal of this study was to explore the impact of written forms of controlling and informational/supportive message framing on motivation and performance in trained cyclists.